The Interplay between Climate Change and Hydroelectricity: Impacts and the Role in Combating Climate Change - Shrestha, Prabin; Khanal, Avishek; Sakhakarmi, Dinesh; Upreti, Drishti; Giri, Suja (Journal of Sustainability and Environmental Management, 2024)
Hydropower plays a crucial role in global energy production and sustainable development, but its reliability and efficiency are increasingly threatened by climate change. This study examined the impacts of climate change on hydropower and its role in combating climate change, with a focus on Nepal. The research gap addressed is the lack of comprehensive studies on the interplay between climate change and hydropower in Nepal. The methodology involved a literature review and analysis of existing policies and projects related to hydropower and climate change adaptation in Nepal. The findings revealed that climate change has led to changes in precipitation patterns, temperature fluctuations, and river flow, affecting the reliability and efficiency of hydropower plants. Despite these challenges, hydropower remains a vital component in combating climate change, offering a clean energy alternative and contributing to sustainable development. The study recommends effective coordination and collaboration with stakeholders, along with the implementation of policies and agreements promoting renewable energy sources like hydropower, to address the challenges posed by climate change and ensure the efficient development and management of hydropower projects in Nepal.